Preparation and characterization of chitosan-coated oleic acid liposomes for intravenous delivery - Noor Ashyfiyah Basrowi,; Vicit Rizal Eh Suk,; Rahadian Permadi,; Misni Misran, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Liposome has been studied as a potential carrier for targeting and controlled drug delivery. However, poor stability remains a challenge because it can lead to drug leakage from the vesicles thus reduce the effectiveness towards the target cell. For this aim, the present study incorporated the low molecular weight chitosan (LMWC) into the oleic acid liposome to maintain the stability and prolong the lifetime in the blood circulation. The thin-film hydration method was employed to prepare the oleic acid liposomes prior to coating them with LMWC. The stability of the liposomes was determined by the measurement of particle size and zeta potential for 28 days. The morphology of the liposome was confirmed by observing the shape under transmission electron microscopy (TEM) and it showed almost spherical in shape. The average particle size increased to 201.23 nm and -51.4 mV when 5 mg of LMWC was added to the oleic acid liposome. The increase of particle size and zeta potential of LMWC-coated liposome indicated that polymer-liposome interaction had changed the stability of liposome thus this invention could be useful for delivering active ingredients through intravenous delivery.